Fundamentals of Entrepreneurship (ENT300) Business Plan : Artisticake / Nurul Hanna Che Rusli - Che Rusli, Nurul Hanna (2020)
Artisticake is a cake shop that offers desserts and services for customers. Artisticake is selling Burnt Cheese Cake. Burnt Cheesecake is a crustless cheesecake that is starting to become a trend in Malaysia. The Burnt Cheesecake is baked at a high temperature in order to get that beautiful burnt exterior and super creamy interior. The bitterness of the burnt exterior mixed with the sweet and creamy interior. Artisticake is located at 40-A, Jalan Todak 2, Bandar Seberang Jaya 13700, Pulau Pinang. Artisticake is a business which focuses on food industry. Bandar Sunway Seberang Jaya is a prime location for most of the employees nearby district businesses. It is easier for us to reach our customer because it is the centre of our target location. Seberang Jaya has a high population density so we grab this opportunity to choose the right place to run the business since Burnt Cheesecake is really hard to find in Seberang Jaya. The opportunity for this business is to be one of marketable product for cake or cheese lover. The location is strategic because it is near with residential area, market and other shops or restaurant. Because of this, people are easy to come and eventually it will attract the customers. The location is also near with the suppliers to our production. Plus, the district also is a location of all major banks in the country, several hotels and shopping mall due to manufacturing area at Seberang Prai. Our client is customers identifying from low to high class who want to eat cakes with affordable price and worthy. We are also adult with family, teenager and we also targeting busiest workers because we are providing delivery service to the customers. Delivery service will be charge depends on the location. Artisticake’s marketing strategy is to emphasize on the quality and price of our product and services. We offer the affordable price so we can fulfill customers’ needs and wants and at the same time we can maximize profit. Thus, we develop marketing strategy that gives attraction for everyone to come to our shop and taste our cakes by themselves. Through the advertisement we already plan to aggressively build our brand through business card, signboard, social media such as Instagram, and providing flyers because that will reach all the population all around Seberang Jaya, Penang. In regards, this will make our product well-known and able to compete with other competitors. We will expect that our business will become more developed in the food industry in Malaysia and the demand for our Burnt cheesecake will increase not only during any occasion but it might be a new daily dessert. This will make our business more profitable and stable in the long run.